2019
DOI: 10.21037/atm.2019.08.105
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoepithelioma-like intrahepatic cholangiocarcinoma with Epstein-Barr virus infection: report of a rare case

Abstract: Lymphoepithelioma-like intrahepatic cholangiocarcinoma (LEL-ICC) is an uncommon lesion.Less than 100 cases of hepatic LELC, including IEL-HCC (hepatocellular carcinoma) and IEL-ICC, have been described, and the understanding of the LELC is very limited. We report the case of a 75-yearold woman with LEL-ICC. She complained of finding a lesion located in the left lateral liver during her last check-up 2 years ago. The contrast-enhanced abdominal computed tomography (CT) scan revealed a low-density mass located i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
30
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 14 publications
1
30
2
Order By: Relevance
“…Epidemiology and clinical characteristics: EBV-associated ICC is very rare and can be divided into 3 types: LELC, conventional-type ICC and LELCC on the basis of the tumor cellular differentiation, and host cellular immune responses in the tumors [12].Indicating that LELCC, which was first reported by Jeng et al [13] in 2001, is a rare variant of ICC. Literature reported, EBER in situ hybridisation was positive in 70% of LELCC cases, while conventional cholangiocarcinomas are not associated with EBV infection [13] According to previous studies, 26 cases of LELCC was analyzed, found that 73.1% (19 of 26) patients were EBV-positive [1,8].These results suggested that LELCC is highly associated with Epstein-Barr virus (EBV) infection [14] and EBV infection might promote the development of LELCC.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…Epidemiology and clinical characteristics: EBV-associated ICC is very rare and can be divided into 3 types: LELC, conventional-type ICC and LELCC on the basis of the tumor cellular differentiation, and host cellular immune responses in the tumors [12].Indicating that LELCC, which was first reported by Jeng et al [13] in 2001, is a rare variant of ICC. Literature reported, EBER in situ hybridisation was positive in 70% of LELCC cases, while conventional cholangiocarcinomas are not associated with EBV infection [13] According to previous studies, 26 cases of LELCC was analyzed, found that 73.1% (19 of 26) patients were EBV-positive [1,8].These results suggested that LELCC is highly associated with Epstein-Barr virus (EBV) infection [14] and EBV infection might promote the development of LELCC.…”
Section: Discussionmentioning
confidence: 93%
“…However,only 26.9% (7 of 26) and 7.7% (2 of 26) LELCC patients were HBV and HCV positive, respectively. This low incidence of HBV and HCV infection suggested that these two viruses might not be significant factors in the pathogenesis of LELCC [8].Despite these findings, the molecular mechanism of EBV, HBV and HCV remain unknown in the tumorigenesis and development of LELCC.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations